The Costs and Benefits of Ownership: A Theory of Vertical and Lateral Integration - Grossman, Sanford J.; Hart, Oliver D. (Journal of Political Economy, 1986)
Our theory of costly contracts emphasizes that contractual rights can be of two types: specific rights and residual rights. When it is costly to list all specific rights over assets in the contract, it may be optimal to let one party purchase all residual rights. Ownership is the purchase of these residual rights. When residual rights are purchased by one party, they are lost by a second party, and this inevitably creates distortions. Firm 1 purchases firm 2 when firm 1's control increases the productivity of its management more than the loss of control decreases the productivity of firm 2's management.